Chinese Agricultural Entrepreneurship in Africa: Case Studies in Ghana and Nigeria - Yang Jiao (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
Agriculture is an important area of Chinese economic engagement in Africa. Since the 1960s, China has provided aid, sent experts, and trained African farmers. However, there is still little empirical research on recent Chinese agribusiness investments in Africa. Drawing on case studies of a private Chinese agribusiness enterprise in Ghana and a Chinese state-owned enterprise in Nigeria, this brief explores the motivation, challenges, and initial social impact of Chinese agricultural investment in Africa.
Keywords: 330